2022
DOI: 10.1002/adhm.202202155
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Targeting Nano‐Systems Targeting Heterogeneous Cancer Cells for Therapeutics and Biomarker Detection

Abstract: Cancer heterogeneity plays a vital part in cancer resistance and metastasis. To provide a reliable approach to exert a therapy action and evaluate its efficiency in heterogeneous cancer cells, a multiple targeting delivery vector composed of histone encapsulating the therapeutic or diagnostic agent, hyaluronic acid targeting CD44 overexpressed in stem tumor cells, SYL3C aptamer targeting epithelial cell adhesion molecule (EpCAM) overexpressed in epithelial cancer cells, and CL4 aptamer targeting epidermal grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…12,37 Currently, nanomedicine-based immunotherapies attempt to target tumor cells, 38,39 cancer mesenchymal fibroblasts, 40 or immune cells. 39,41,42 The immunological activity of multi-targeted nano pharmaceuticals therapy 28,43 is greater than that of single-targeted nanoparticles for tumor cells. 44 ATF@Pt Lps were successfully prepared in our study, and in vitro tumor sphere infiltration and live imaging experiments demonstrated that liposomes modified with ATF peptides enriched drugs in deep tumors, suggesting that the ATF peptide targets mesenchymal tumor and cancer cells and disrupts the stromal barrier, decreasing the expression of α-SMA, collagen I, and fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…12,37 Currently, nanomedicine-based immunotherapies attempt to target tumor cells, 38,39 cancer mesenchymal fibroblasts, 40 or immune cells. 39,41,42 The immunological activity of multi-targeted nano pharmaceuticals therapy 28,43 is greater than that of single-targeted nanoparticles for tumor cells. 44 ATF@Pt Lps were successfully prepared in our study, and in vitro tumor sphere infiltration and live imaging experiments demonstrated that liposomes modified with ATF peptides enriched drugs in deep tumors, suggesting that the ATF peptide targets mesenchymal tumor and cancer cells and disrupts the stromal barrier, decreasing the expression of α-SMA, collagen I, and fibronectin.…”
Section: Discussionmentioning
confidence: 99%